Financial Liquidity Management Strategies in Polish Energy Companies - Zimon, Grzegorz (International Journal of Energy Economics and Policy, 2020)
Financial liquidity is the foundation for building a strong enterprise. Every small or large enterprise, regardless of the industry, needs to have financial liquidity to grow. Its management is complicated as it is related to current assets, short-term liabilities and profitability. The existing relationship between profitability and liquidity makes it very difficult to choose the right liquidity management strategy. The purpose of the article is to analyze the strategy of managing liquidity in state-owned enterprises operating in the energy sector. In this industry in Poland in recent years there has been a high increase in costs related to fees for CO2 emissions, which will have the large impact on the profitability of enterprises, which will hinder the choice of financial liquidity management strategies. The specificity of the industry, the form of ownership of the analyzed enterprises and the government's policy will also have a significant impact on the shape of the liquidity management policy. The analysis was based on the financial statements for 2015-2018. Keywords: financial liquidity, energy companies, strategy JEL Classifications: G10; G33; Q43 DOI: https://doi.org/10.32479/ijeep.9150